Koordinasi Dalam Penanganan Banjir Pada Daerah Irigasi Desa Pematang Cermai Kecamatan Tanjung Beringin Kabupaten Serdang Bedagai - Sitorus, Pinta Uli; Ridwan Rangkuti, Mohammad (JURNAL ADMINISTRASI & MANAJEMEN, 2024)
This study aims to determine and describe the coordination of the local government (Irrigation Commission) in flood management efforts in Hamlet II, Pematang Cermai Village, Tanjung Beringin District, Serdang Bedagai Regency. The Irrigation Commission consists of the PUTR Office, the Agriculture Office and P3A. The importance of this research is to be able to find out the steps or ways taken by the government in the context of handling floods and optimizing irrigation. In addition, this research is also useful so that farmers know how to overcome problems caused by floods in rice fields. This research uses descriptive research method with qualitative approach. Data collection techniques were carried out through interviews, observations and literature studies, with 12 total research informants consisting of the Irrigation Commission, PUTR Office, Agriculture Office, Water User Farmers Association, and farmers of Dusun II, Pematang Cermai Village. The results showed the following: First, the Irrigation Commission has not run optimally; Second, rice production has increased, but farmers' income has decreased; Third, unity of action, communication, division of labor and discipline that is still not running optimally, Fourth, it is necessary to improve agricultural infrastructure and technology.